Is patriarchal regime in Myanmar changing? - Eliška Boháčová (Annales Scientia Politica, 2018)
After the elections in November 2015 Myanmar has had a new and, although some wouldn’t agree, democratic government. And the head of the new government is a woman – Aung San Suu Kyi. In a country where the government had been led by an army dominated by men for more than five decades, there is now a quasi-democratic government led by a woman. Could this fact imply that the situation of Myanmar’s women in general is improving? Does democratization have any implications for a gender regime that has been dominantly patriarchal for decades? And how do the democratisation process and the rising Buddhist nationalism effect the antidiscrimination agenda declared after the abandonment of military rule?